Stock-based managerial compensation, price informativeness, and the incentive to overinvest - Strobl, Günter (Journal of Corporate Finance, 2014)
This paper investigates the relationship among a firm's managerial incentive scheme, the informativeness of its stock price, and its investment policy. It shows that the shareholders' concerns about the effectiveness of stock-based compensation can lead to overinvestment. However, unlike other explanations in the literature, our results are neither caused by suboptimal incentive contracts nor do they rely on the assumption that managers are “empire builders.” Rather, overinvestment serves to induce information production by outside investors. By accepting positive and negative NPV projects, a firm effectively increases the market's uncertainty about its cash flow, thereby giving traders more incentives to become informed.